The Impact Of Globalization On Cities - BEYHAN KARA (Journal of Contemporary Urban Affairs, 2019)
A lot of cities nowadays are changing substantially due to the influence of globalization. The most significant impact of globalization is in cities because the cities are becoming the rulers of the countries. In this process, a variety of urban developments on different platforms are awaiting cities. These developments are discussed in different dimensions. Here, the globalization process and the effects this process has on the understanding of city management, urban space and urban law are tried to be revealed. In sum, the effects of globalization on cities and the concept of world cities are forming. In the context of problems of globalization, the effects of globalization on economic, cultural, social, spatial and environmental values and understanding of management are examined. It was established that globalization also includes the increased movement of people, products, ideas, images, lifestyles, policies and capital and that it affects cities through local and global dynamics which in turn causes macro-urban and micro-urban changes. Conclusions were made that globalization tends to affect a lot of spatial, economic and social patterns which in turn affects cities but does not result in the same spatial patterns.